Amaranthus saradhiana (Amaranthaceae)—a new species from southern Western Ghats of Kerala, India - Arya, Sindu; Kumar, Venugopalan Nair Saradamma Anil; Vishnu, Walsan Kalarikkal; Kumar, Thaliyangal Rajesh (Phytotaxa, 2019)
A new species of Amaranthus from the southern region of Kerala, India is described and illustrated as Amaranthus saradhiana sp. nov. SEM analysis of pollen and seed architectural patterns together with FTIR spectral banding discriminates the taxon from its morphologically allied species, A. spinosus. Detailed description including distribution with relevant taxonomic notes along with color photographs and sketches are provided.